Reliability, availability, maintainability and safety (RAMS) components and potential: A review - Muhammad Azri, Muhammed Nor; Ahmad Fitri, Yusop; Mohd Adnin, Hamidi; Mohd Nadzeri, Omar; N. A., Abdul Hamid; W. M., Wan Mohamed (UTeM, 2022)
RAMS implementation in Railway System is still developing and caught the attention of many researchers and institutions. The information about application of RAMS in other industries such as petroleum, chemical and avionic is already matured and widely implemented. The discussion and publication of railway RAMS need to be encouraged and continued. As railway authority started to make RAMS analysis compulsory for all phase of railway life cycle, it is important to bundle and address the component together rather than as individual discipline. This paper extracts all the important components an equation regarding RAMS.